Optimizing forage harvest and the nutritive value of Italian ryegrass-based mixed forage cropping under northwestern Himalayan conditions - Kumar, Naveen; Singh, Rajender; Agrawal, Rajiv Kumar; Sharma, Gurbhan Dass; Singh, Akashdeep; Sharma, Tarun; Rana, Ranbir Singh (Frontiers in Plant Science, 2024)
The scarcity of high-quality forage has a significant influence on the productivity and profitability of livestock. Addressing this concern, an investigation was undertaken to assess the effects of distinct Italian ryegrass genotypes, namely Punjab ryegrass-1, Kashmir collection and Makhan grass, in conjunction with varying seeding ratios of Italian ryegrass to Egyptian clover. The seeding ratios considered were 100:0 (Italian ryegrass to Egyptian clover), 75:25, 50:50, and 25:75. All possible combination of Italian ryegrass and Egyptian clover with seeding ratios were set up in a Randomized complete block design and replicated thrice. Co-cultivating Italian ryegrass and Egyptian clover at a 75:25 seeding ratio yields the best yield benefit, as determined by the land equivalent ratio. It is noteworthy that in this configuration, real yield loss is higher for Egyptian clover and for Italian ryegrass when the seeding ratio is 25:75. The higher competitiveness of Italian ryegrass in comparison to Egyptian clover is highlighted by the competitive ratio. Notably, the nutritive parameter, crude protein yield, was significantly higher in the Makhan grass-based 50:50 and 75:25 seeding ratio. The outcomes of this study revealed that the 100:0 seeding ratio, coupled with the Makhan grass genotype, exhibited superior performance in terms of cumulative forage harvest, dry matter accumulation, net returns, and benefit cost ratio.